2019
DOI: 10.1080/09168451.2019.1584522
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Lactobacillus brevis associated with decrease in pH by glucose fermentation

Abstract: Some Lactobacillus brevis strains were found to aggregate upon the addition of glucose, which resulted in glucose fermentation and pH decrease. Surface layer proteins (Slp) that represented the outermost layer of the bacteria decreased under these low pH conditions, probably because of the partial detachment of Slp from the cell surface triggered by the acidic environment. Similar observations of decreased Slp and aggregation were observed under the culture conditions, confirming that L. brevis aggregation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Auto-aggregation appears to be the first step in the adhesion process, allowing bacteria to form a barrier and prevent the adhesion of undesirable bacteria [18]. Cell surface hydrophobicity is another property considered important in overall adhesion capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Auto-aggregation appears to be the first step in the adhesion process, allowing bacteria to form a barrier and prevent the adhesion of undesirable bacteria [18]. Cell surface hydrophobicity is another property considered important in overall adhesion capacity.…”
Section: Introductionmentioning
confidence: 99%
“…W. Wang et al (2018) investigated the effect of initial acid and alkali stress on autoaggregation, protein adhesion, and cell adhesion of L. plantarum, and the results showed that the autoaggregation, adhesion to HT-29 cell lines, and the expression level of adhesion-related proteins of L. plantarum were all increased under initial acid stress, whereas the reverse occurred under initial alkali stress. However, the induction of Lactobacillus brevis aggregation by decreasing pH during fermentation by using glucose as a carbon source was attributed to the partial detachment of surface layer proteins and the formation of irregular charges across the cell surface (Saito et al, 2019). In addition, oxygen concentration is also an important controlling parameter in fermentation.…”
Section: Environmental Factors Affecting Microbial Aggregationmentioning
confidence: 99%
“…This was further resolved if there is better bacterial adhesion to hydrocarbons (BATH), cellular auto-aggregation, and salt aggregation. BATH deals with the adhesion property of strain and both cellular autoaggregation and salt aggregation are clumping or self-aggregation capacity of cells related to its persistence (Saito et al, 2019), Probiotic has also been reported for their hypocholesterolemic activity which can be attributed to bile salt hydrolase (bsh) activity (Huang et al, 2019;Kumar et al, 2012). It is an enzymatic breakdown or deconjugation of bile salts or bile acids by probiotic LAB, increases its excretion or decrease its reabsorption (Ishimwe et al, 2015), and can be attributed to in vivo lowering of serum cholesterol levels (Patel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This was further resolved if there is better bacterial adhesion to hydrocarbons (BATH), cellular auto‐aggregation, and salt aggregation. BATH deals with the adhesion property of strain and both cellular auto‐aggregation and salt aggregation are clumping or self‐aggregation capacity of cells related to its persistence (Saito et al., 2019 ),…”
Section: Introductionmentioning
confidence: 99%